Research trends relating to body weight control: a systematic review and keyword network analysis of Korea Citation Index Journals (2004–2023) - Yunkyoung Oh; Eunsil Her (Korean Journal of Community Nutrition)
Objectives Obesity rates are rapidly rising in Korea. Weight control is highly involved in obesity treatment. This study aimed to explore research trends related to weight control through keyword network analysis. By focusing on journals indexed in the Korea Citation Index (KCI), this study highlights trends specific to Korea, offering insights that reflect the country’s unique cultural and policy contexts in weight control research. Methods This study collected keywords from weight control-related papers published in the KCI journal over the past 20 years. Keywords were cleaned through Textom (2024), and the relationships between key research issue frequency analysis, structural characteristics, and keywords were identified using Textom, UCINET6, and NetDraw. Results Over the past 20 years, 40 to 50 studies related to weight control have been conducted each year. The Korean Journal of Community Nutrition had the largest number of published articles. Keyword frequency analysis showed that ‘obesity’ had the highest frequency. And the analysis of degree centrality and betweenness centrality, the keyword ‘obesity’ ranked the highest. CONCOR analysis identified four clusters: preventive health care, health management, physical health, and personal development. Conclusion The results of this study showed that weight control research reflecting the characteristics of the times has been steadily progressing in relation to the rapidly increasing obesity in Korea, and when developing policies or setting research directions related to weight loss in the future, research should be conducted in a prospective manner by subdividing it according to groups and interests.